Strategi Pr Digital Berbasis Excellence Di Unilever - Mariska, Ririn; Ghanystyana, Lathifa Prima; Fadilah, Haris Tammam; Maryani, Maryani; Haryati, Rima (Syntax Corporation, 2025)
The role of technology in improving Public Relations (PR) strategies in the digital era is crucial, because technology allows organizations to communicate more effectively and responsively with audiences. By utilizing social media, analytical tools, and artificial intelligence, PR can build a positive image, manage reputation, and deliver relevant and timely information, thereby strengthening relationships with the public and increasing engagement. Technology has significantly changed the Public Relations (PR) landscape in the digital era, where fast and efficient communication is the key to success. The use of social media as a primary platform allows organizations to interact directly with audiences, disseminate information, and manage reputation in real-time. In addition, analytical tools provide deep insights into audience behavior, allowing for more targeted strategy adjustments. Artificial intelligence also plays a significant role in accelerating the communication process and increasing creativity, with the ability to analyze public sentiment and respond to emerging issues quickly. Thus, the integration of technology in PR strategies not only increases efficiency but also strengthens relationships with the public, providing a competitive advantage for organizations that are able to adapt to these changes.